2019
DOI: 10.3390/su11164407
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Artificial Neural Networks and Decision Trees to Predict the Degree of Odor Nuisance of Post-Digestion Sludge in the Sewage Treatment Plant Process

Abstract: This paper presents the application of artificial neural networks and decision trees for the prediction of odor properties of post-fermentation sludge from a biological-mechanical wastewater treatment plant. The input parameters were concentrations of popular compounds present in the sludge, such as toluene, p-xylene, and p-cresol, and process parameters including the concentration of volatile fatty acids, pH, and alkalinity in the fermentation sludge. The analyses revealed that the implementation of artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Because both real datasets we consider here are not very large (i.e., 303 records in each of them), we can use the K-fold cross-validation technique which is generally very effective with this kind of data. By using the K-fold cross-validation technique, the problem of data bias can be minimized [44]. As mentioned previously, our base nu-SVC algorithm was used with four different kernel functions (linear, polynomial, RBF and sigmoid).…”
Section: Algorithm 1 a General Nested Ensemble (Ne) Modelmentioning
confidence: 99%
“…Because both real datasets we consider here are not very large (i.e., 303 records in each of them), we can use the K-fold cross-validation technique which is generally very effective with this kind of data. By using the K-fold cross-validation technique, the problem of data bias can be minimized [44]. As mentioned previously, our base nu-SVC algorithm was used with four different kernel functions (linear, polynomial, RBF and sigmoid).…”
Section: Algorithm 1 a General Nested Ensemble (Ne) Modelmentioning
confidence: 99%
“…The ANN for the prediction of odor properties of post-fermentation sludge from a biological-mechanical wastewater treatment plant was developed. The ANN comprised of four layers: input layer (eight neurons), two hidden layers (four and two neurons) and output layer (one neuron) [51]. In medicine, ANNs are used to predict mortality risk and incidence of disease.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that AI-based models are reliable and full-scale in forecasting horizons. Bylinski et al [56] concluded that using an artificial neural network (ANN) grants a great reflection of complex dependencies of the wastewater management problems, without considering detailed mechanisms of specified processes.…”
Section: Introductionmentioning
confidence: 99%